The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1038/bmt.2012.4
|View full text |Cite
|
Sign up to set email alerts
|

Allo-SCT for AML and MDS with treosulfan compared with BU-based regimens: reduced toxicity vs reduced intensity

Abstract: Allo-SCT with reduced-intensity conditioning (RIC) results in lower non-relapse mortality (NRM), but higher relapse rate than myeloablative conditioning (MAC) in AML/myelodysplastic syndromes (MDS). Novel regimens with intensive anti-leukemic activity, but with limited toxicity will be of benefit. In all, 85 patients with AML/MDS, not eligible for MAC, were given fludarabine-treosulfan conditioning (FT). Outcomes were compared with those in patients given fludarabine-BU RIC (FB2, n ¼ 106) or reduced-toxicity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
2
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 28 publications
7
39
2
1
Order By: Relevance
“…39 However, chronic GvHD rates are similar after FT and other RIC or MAC regimens. 29,40 Similar to other studies advanced age, comorbidities, unrelated donor and chemo-refractory disease were also associated with higher NRM.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…39 However, chronic GvHD rates are similar after FT and other RIC or MAC regimens. 29,40 Similar to other studies advanced age, comorbidities, unrelated donor and chemo-refractory disease were also associated with higher NRM.…”
Section: Discussionsupporting
confidence: 72%
“…We have compared FT with busulfan based RIC or MAC regimens in patients with AML and myelodysplastic syndromes. 29 FT was associated with similar NRM as RIC, but controlled leukemia better, resulting in better outcome in patients with advanced disease at SCT. There are only limited data on the use of FT in lymphoid malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, brain exposure to drugs could be associated with neurologic adverse effects, for instance seizures. Beneficially, in clinical trials high-dose TREO demonstrated low neurotoxicity in adults as well as children, at least in comparison with high-dose busulfan, requiring anticonvulsive prophylaxis (Wachowiak et al, 2011;Casper et al, 2012;Danylesko et al, 2012;Shimoni et al, 2012;Boztug et al, 2015). Nevertheless, in one pediatric study (n = 70, including 46 infants), seizures occurred in four infants aged #4 months (Slatter et al, 2011).…”
Section: Penetration Of Treosulfan and Its Monoepoxide Into Cnsmentioning
confidence: 99%
“…Probably, TREO provides lower organ toxicity than busulfan, especially hepato-, pulmo-, and neurotoxicity. One hypothesis that needs experimental verification assumes that because of lower lipophilicity of TREO compared with busulfan, the former achieves lower concentrations in those key organs and, consequently, is less toxic (Główka et al, 2010;Danylesko et al, 2012;Shimoni et al, 2012). The underlying mechanism of potentially low neurotoxicity of TREO appears particularly important for infants, as maturity of their blood-brain barrier (BBB) is still unknown (Saunders et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation